Experimental Investigation of Dynamic Compression Mechanical Properties of Frozen Fine Sandstone - Jiehao Wu; Haibo Wang; Qi Zong; Ying Xu (Advances in Civil Engineering)
Aiming at the dynamic mechanical properties of weakly cemented fine sandstone in the rich water-bearing strata in western China under dynamic loading, a 50 mm rod diameter separation Hopkinson pressure bar (SHPB) test was used to study the Paleogene fine sandstone in a coal mine in Ningxia. The system carried out the impact compression tests of −15°C, −20°C, and −30°C and the average strain rate of 28 s−1–83 s−1 and obtained the dynamic compressive strength of the frozen fine sandstone specimens under different test conditions. The strain curve and the fracture morphology were analyzed for the relationship between dynamic peak stress, peak strain, dynamic strength growth coefficient (DIF), and fracture morphology and strain rate. The results show that the peak stress of frozen fine sandstone increases from the decrease of freezing temperature under the same average strain rate. The peak stress of the specimen increases from the increase in the average strain rate of the same freezing temperature. The failure modes of specimen are mainly divided into axial splitting tensile failure and compression crushing failure. To the splitting tensile failure and the compression crushing failure, the main factors determining the two failure modes are the strain rate, while the temperature affects the severity of the impact damage. In the load strain rate and temperature range, the DIF of the frozen fine sandstone is linearly correlated with the strain rate, and the lower the temperature, the slower the growth rate of the DIF.